XX ӘСИРДИҢ АҚЫРЫ XXI ӘСИРДИҢ БАСЫНДАҒЫ ҚАРАҚАЛПАҚ БАЛАЛАР ПОЭЗИЯСЫНДА ЮМОР-САТИРА - Казахбаев, С.С. (FAN va JAMIYAT, 2017)
In the article humor and satire are analyzed in the poetry of Karakalpak children at the end of the XXth and at the beginning of XXI century. Humor and satire play a great role in children’s poetry. The author studied destinguishing features of the poems of S.Abbazov, E.Akimbaev, A.Khalmuratov, Ya.Ajimov, U.Sarsebaev, J.Dilmuratov and defined the ideological-artistic and thematic peculiarities of Karakalpak poetry for children.